2017
DOI: 10.1371/journal.pone.0176533
|View full text |Cite
|
Sign up to set email alerts
|

Lys48 ubiquitination during the intraerythrocytic cycle of the rodent malaria parasite, Plasmodium chabaudi

Abstract: Ubiquitination tags proteins for different functions within the cell. One of the most abundant and studied ubiquitin modification is the Lys48 polyubiquitin chain that modifies proteins for their destruction by proteasome. In Plasmodium is proposed that post-translational regulation is fundamental for parasite development during its complex life-cycle; thus, the objective of this work was to analyze the ubiquitination during Plasmodium chabaudi intraerythrocytic stages. Ubiquitinated proteins were detected dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…We find that mutations in Pfcoronin alter the regulation of Pf Actin, including changes in quantity and in ubiquitination status. These findings are consistent with a previous study in P. chabaudi , where actin was among one of three proteins identified to be ubiquitinated in ring-stage parasites 26 . Studies in other organisms have also reported ubiquitination of actin 27 , and ubiquitin has been shown to play a role in actin homeostasis 28 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We find that mutations in Pfcoronin alter the regulation of Pf Actin, including changes in quantity and in ubiquitination status. These findings are consistent with a previous study in P. chabaudi , where actin was among one of three proteins identified to be ubiquitinated in ring-stage parasites 26 . Studies in other organisms have also reported ubiquitination of actin 27 , and ubiquitin has been shown to play a role in actin homeostasis 28 .…”
Section: Discussionsupporting
confidence: 93%
“…chabaudi, where actin was among one of three proteins identified to be ubiquitinated in ring-stage parasites 26 . Studies in other organisms have also reported ubiquitination of actin 27 , and ubiquitin has been shown to play a role in actin homeostasis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitin sequence has seven lysine residues at positions 6, 11, 27, 29, 33, 48 and 63, and each of these, as well as the N-terminal α-amino group, is a potential ubiquitylation site. In Plasmodium chabaudi the importance of Lys48 ubiquitylation has been highlighted [15]. When ubiquitin of either host or parasite origin is digested with trypsin, diGly-remnant peptides cannot be distinguished, except for those modified at position 11 or 27 for which the Asp/Glu polymorphism differentiates host-and parasite-derived sequences.…”
Section: Introductionmentioning
confidence: 99%
“…A known PTM of actin is acetylation, performed by aminopeptidases that remove the N -terminal methionine and modify the immediate subsequent amino acids (Rubenstein and Martin, 1983). The ubiquitination of actin (arthrin) has been reported in arthropods (Bullard et al , 1985; Burgess et al , 2004) and in PfACT1 (Field et al , 1993; González-López et al , 2017). Other PTMs such as arginylation (Karakozova et al , 2006), phosphorylation (Kishi et al , 1998; Gu et al , 2003), carbonylation (Castro et al , 2012), s -nitrosylation (Lu et al , 2009), methylation (Nyman et al , 2002), glutathionylation (Sakai et al , 2012) and sumoylation (Alonso et al , 2015) were characterized in actin.…”
Section: Discussionmentioning
confidence: 99%